2021
DOI: 10.1136/bmjdrc-2020-001819
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with missed appointments by adults with type 2 diabetes mellitus: a systematic review

Abstract: Keeping regular medical appointments is a key indicator of patient engagement in diabetes care. Nevertheless, a significant proportion of adults with type 2 diabetes mellitus (T2DM) miss their regular medical appointments. In order to prevent and delay diabetes-related complications, it is essential to understand the factors associated with missed appointments among adults with T2DM. We synthesized evidence concerning factors associated with missed appointments among adults with T2DM. Using five electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…About 12 -36% of patients with type 2 diabetes missed regular appointments. Understanding the distributing factors of regular appointments can improve diabetes care in patients with diabetes (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 12 -36% of patients with type 2 diabetes missed regular appointments. Understanding the distributing factors of regular appointments can improve diabetes care in patients with diabetes (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Results of this review showed that a variety of multilevel factors is associated with an irregular appointment in this population with inconsistency in findings. They found that most of the published reports examined patients' features and ignored the role of interpersonal factors (14). Davoodi et al in a Qualitative Study explored barriers and incentive factors for patients with type 2 diabetes to refer urban health center of Ahvaz.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with inadequate adherence to medication and self-monitoring of blood glucose and suboptimal glycemic control, which all contribute to life-threatening diabetes-related complications [40]. Systematic reviews have identified several factors associated with clinic nonattendance, including patient factors (e.g., socioeconomic status, knowledge, health literacy, and health beliefs, and perceptions), disease-related factors (e.g., treatment regimen, comorbidities, and HbA1c level), and healthcare provider factors (e.g., poor communication, long interval to appointment, and healthcare provider's attitudes and behaviors) [38,[41][42][43]. Healthcare providers and systems should utilize a range of interventions that are known to reduce clinic nonattendance both at the patient level (e.g., SMS and telephone reminders) and the healthcare system level (e.g., clinician continuity, efficient register, and recall system and online clinics) [38,41,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…On a broader scale, a history of trauma is also associated with distrust in healthcare systems (Klest et al, 2019). Given that negative interpersonal interactions with healthcare personnel are associated with non-attendance at diabetes outpatient appointments (Sun et al, 2021), improving the quality of interactions between patients, providers, medical staff, and healthcare administrators should remain a priority. Moreover, the quality of patients' routine care experiences beyond the exam room warrants attention, including checking of vital signs and current medication list review, check-in and interactions with office reception, appointment reminders, waiting room signage, verbiage on pre-visit screening questionnaires, website and social media messaging, referral process, and prescription refill reminders.…”
Section: Ace Subtypes and Diabetes Care Usementioning
confidence: 99%